The impact of grain maize and sunflower as previous crops on the yield and ear number of winter wheat in a long-term experiment - Szilágyi, Gergely (Acta Agraria Debreceniensis, 2015)
We have analyzed the effect of grain maize and sunflower forecrop on three different winter wheat genotype (GK Csillag, Mv Csárdás, Mv Toldi) regarding to the spike number and yield in different fertilization levels in the 2012/2013 cropyear. According to our data after sunflower forecrop we reached higher spike number and yield, which were influenced by the differences of the varieties. We found significant differences between the varieties in the control treatment. According to our research, GK Csillag has reached the highest yield in the examined fertilization levels and forecrop models too.